1969
DOI: 10.1152/ajplegacy.1969.216.3.567
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins and consecutive vascular segments of the canine hindlimb

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…A number of previous studies have demonstrated the contractile effect of PGF2a both in cerebral (Toda, 1976;Edvinsson, Hardebo, McCulloch & Owman, 1978;Uski, Edvinsson & Owman, 1981) and peripheral vessels (Nakano, 1968;Greenberg & Sparks, 1969). The maximum contractile effect of PGF2.…”
Section: Discussionmentioning
confidence: 94%
“…A number of previous studies have demonstrated the contractile effect of PGF2a both in cerebral (Toda, 1976;Edvinsson, Hardebo, McCulloch & Owman, 1978;Uski, Edvinsson & Owman, 1981) and peripheral vessels (Nakano, 1968;Greenberg & Sparks, 1969). The maximum contractile effect of PGF2.…”
Section: Discussionmentioning
confidence: 94%
“…PGE1 has been reported to relax the contraction of vascular smooth muscle cells [61] and increase blood flow in peripheral arteries [62] , followed by improvement of endothelial function [63] . Since PGE1 is rapidly inactivated in the lungs, PGE1 must be administered into the obstructed artery or a large amount of it has to be given intravenously.…”
Section: Effect Of Prostaglandin-e1 To Normal Nerve Root and Compressmentioning
confidence: 99%
“…The failure to elicit a response upon subsequent injections of prostaglandin E2 may be due to the limb vasculature being maximally dilated as suggested by Daugherty (1971). In contrast to the studies of Ducharme, Weeks & Montgomery (1968) and Greenberg & Sparks (1969), prostaglandin F2.did not induce vasoconstriction in the isolated hind limb. However, the techniques employed by these investigators were substantially different.…”
Section: Methodsmentioning
confidence: 81%